Orientalism or Meridionism? British identity formation through travel writing on India and Italy, 1760-1850 - Robinson, David (2020)
This thesis compares two bodies of travel writing; the accounts of ‘middling types’ of British travellers to Italy and to India from the late eighteenth to the mid-nineteenth centuries. Rather than treat British engagement with these two travel destinations separately, as has tended to be the case, I consider the ways in which British travel to Italy and India contributed to and justified an emerging sense of British identity, which reflected the growing cultural and political authority of the middle-classes.